Towards a "literary" translation of the Scriptures: with special reference to a "poetic" rendition - E. R. Wendland (Acta Theologica)
This study proposes a more dynamic, or “mediated,” approach to Bible translation as one possible option (among many), should this be called for by the contextual circumstances of the target language setting. Such a method features a genre-based, functional application of interlingual discourse analysis and representation that aims to reproduce the literary (especially the “poetic”) quality and energy of the original text (certain aspects of its structure, style, impact, and appeal) within a new linguistic and sociocultural environment. The importance of this local milieu requires the active participation of the target language community during the formulation and execution of an appropriate translation brief, or planning document, including the project’s principal communicative purpose (skopos). Another important ariable to be examined is the primary channel of textual representation. Here, the oral-aural mode is emphasised due to its particular relevance in Africa. My presentation concludes with an overview of some of the critical cost-versus-gain factors that need to be considered when planning for the production of a literary version.